Effect of vaginal lubricants on sperm motility and chromatin integrity: a prospective comparative study - Agarwal, Ashok; Deepinder, Fnu; Cocuzza, Marcello; Short, Robert A.; Evenson, Donald P. (Fertility and sterility, 2008)
To evaluate the effect of vaginal lubricants Pre∼Seed, FemGlide, Astroglide, and Replens on human sperm motility and chromatin integrity. Prospective, comparative, in vitro study. Andrology laboratory at tertiary care hospital. Thirteen normozoospermic donors. Semen samples from 13 subjects were incubated in human tubal fluid media (HTF) controls and 10% (vol/vol) of Pre∼Seed, FemGlide, Astroglide, and Replens lubricants. After 30 minutes, progressive sperm motility was assessed by light microscopy. Semen samples of 12 patients were placed in positive control (HTF), negative control (10% K-Y Jelly lubricant), and 10% vol/vol Pre∼Seed and FemGlide lubricants. After 4 hours culture, spermatozoa were analyzed for percent DNA fragmentation index with use of the acridine orange–based sperm chromatin structure assay. Sperm motility and percent DNA fragmentation index. Percent motility did not differ significantly between HTF controls and Pre∼Seed, whereas FemGlide, Replens, and Astroglide lubricants demonstrated a significant decrease in motility. There was no significant difference in percent DNA fragmentation index between the HTF controls and Pre∼Seed, but a significant decline in sperm chromatin quality occurred with FemGlide and K-Y Jelly. Pre∼Seed does not cause a significant decrease in progressive sperm motility or chromatin integrity in contrast to other lubricants used by couples.